Performance enhancing in the manufacturing industry: an improvement KATA application - Dinis-Carvalho, José (2016)
As manufacturing firms (MFs) experience increasing competition in the global economy, it is vital to seek competitive advantage through the continuous improvement of performance within manufacturing processes. This requires a systematic approach to enhance performance by engaging staff at all levels to effectively take part in performance-enhancing efforts. The implementation of Toyota Kata has been proven to be highly successful for continuous improvement in a MF. Toyota Kata provides a holistic system of methods for improving performance, which contains processes and behavioral patterns for strategically aligned goal setting, problem solving, coaching, management and training. It is a simple and human factor focused approach, which covers the management of performance improvement efforts. This manuscript presents a case study performed in a wooden frames manufacturing firm for the implementation of Improvement Kata. Lead time has been selected as the performance indicator. The study describes current challenges, Improvement Kata implementation methodology, and the lead time improvement results.